2020
DOI: 10.1108/ecam-04-2020-0221
|View full text |Cite
|
Sign up to set email alerts
|

Optimising social procurement policy outcomes through cross-sector collaboration in the Australian construction industry

Abstract: PurposeSocial procurement policies are an emerging policy instrument being used by governments around the world to leverage infrastructure and construction spending to address intractable social problems in the communities they represent. The relational nature of social procurement policies requires construction firms to develop new collaborative partnerships with organisations from the government, not-for-profit and community sectors. The aim of this paper is to address the paucity of research into the risks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…[38][39][40] stated, social value is inherently 'subjective, malleable and variable' in nature and means different things to different people based on their ethics, morals, and priorities. This is especially true in construction, where the potential social value of social procurement is undermined in practice by stakeholder nervousness about policy design, stability and implementation, poor risk management, information asymmetries, and perverse incentives [22]. Social procurement in construction is also inconsistent because practices are not internalised across organisations, and projects and the people targeted by social procurement may only be hired on to comply with contractual social procurement requirements [23].…”
mentioning
confidence: 99%
“…[38][39][40] stated, social value is inherently 'subjective, malleable and variable' in nature and means different things to different people based on their ethics, morals, and priorities. This is especially true in construction, where the potential social value of social procurement is undermined in practice by stakeholder nervousness about policy design, stability and implementation, poor risk management, information asymmetries, and perverse incentives [22]. Social procurement in construction is also inconsistent because practices are not internalised across organisations, and projects and the people targeted by social procurement may only be hired on to comply with contractual social procurement requirements [23].…”
mentioning
confidence: 99%
“…While this supports other research which highlights the importance of formal power in championing innovations like social procurement (Jenssen and Jørgensen, 2004), our results also raise new questions which need further investigation, about the role of business size in implementing social procurement. On one hand, this seems to conflict with Loosemore et al. (2020a) who found that smaller construction firms are more sceptical about social procurement than larger firms.…”
Section: Resultsmentioning
confidence: 87%
“…People that bring leadership qualities such as integrity, and empathy and courage and the like (R2). Finally, adding to the very limited construction social procurement research into the enablers of cross-sector collaboration of social procurement policies (Loosemore et al, 2020a), respondents also highlighted the importance of being able to identify potential partners with the necessary skills, competencies and values to be able to collaborate effectively. This was based on trial and error and experience (good and bad) of working with various partners over multiple projects.…”
Section: Ecam 309mentioning
confidence: 99%
See 1 more Smart Citation
“…Relationships within construction sites have limited time to develop before they accomplish the project and change to another project. The challenges of operating in transitionary project-based environments are distinct from stable environments (Loosemore et al, 2020 ). Construction firms in developing countries are challenged with both organisational and country-level uncertainties.…”
Section: Study Context: Construction Industry In Sri Lankamentioning
confidence: 99%